Nutraceutical formulations and natural compounds for the management of chronic diseases - Fatima, Ghizal; Khan, Sadaf; Shukla, Vani; Awaida, Wajdy; Li, Duo; Gushchina, Yulia Sh (Frontiers in Nutrition, 2025)
Chronic non-communicable diseases including cancer, diabetes, cardiovascular, neurodegenerative, and autoimmune disorders pose mounting global health and economic challenges. Conventional drugs often focus on symptom management, frequently accompanied by side effects and rarely reversing disease progression. Nutraceuticals bioactive compounds sourced from foods, herbs, and marine organisms, offer a promising alternative due to their inherent anti-inflammatory, antioxidant, immunomodulatory, neuroprotective, and cardioprotective properties. This review synthesizes current evidence on key nutraceutical classes (e.g., polyphenols, flavonoids, omega-3 fatty acids, probiotics, plant alkaloids), elucidating their molecular mechanisms such as oxidative stress mitigation, immune modulation, gene regulation, and signaling pathway interactions and highlighting therapeutic applications across major chronic conditions. Addressing a critical limitation, we analyze advanced delivery technologies (e.g., nano-formulations, encapsulation, liposomes, micro- and hydrogels, co-administered bioenhancers) designed to enhance bioavailability and targeting. We also discuss navigating hurdles such as regulatory inconsistencies, safety concerns, herb–drug interactions, and the need for standardization. To fully incorporate nutraceuticals into modern healthcare, the review emphasizes the imperative for rigorous clinical validation, manufacturing quality control, and long-term safety monitoring. Finally, we propose future directions including personalized nutraceutical strategies, AI-assisted discovery, and global regulatory harmonization positioning nutraceuticals as sustainable and evidence-based adjuncts or alternatives in chronic disease management.